Which specific modes of exercise training are most effective for breast related cancer fatigue? Network meta-analysis - Li, Ying; Zhang, Jianhua; Hu, Di; Gao, Lei; Huang, Ting (Frontiers in Oncology, 2025)
ObjectiveThe objective of this study was to examine the impact of various exercise modalities on Cancer-Related Fatigue (CRF) among breast cancer patients.MethodsA computerized search was conducted on databases including PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, and Wanfang Database up to October 2023. Selection criteria were applied to include or exclude studies, resulting in the inclusion of 65 articles for comparison of the effects of 12 distinct exercise interventions on individuals with breast cancer.ResultsThe 65 studies used 12 different measures of exercise. Network meta results show that Compared with Other exercise (OE), Baduanjin exercise (BE), Qigong (QG), Control group (CG), Tai Chi (TC) improved significantly in CFR. The effect of Yoga (YG) on improving sleep quality is better than Control group (CG) and Baduanjin exercise (BE). Compared with Control group (CG), Tai Chi (TC) and Yoga (YG) are more beneficial to improve the quality of life of breast cancer patients. Tai Chi (TC) is better than Multimodal exercise (ME), Other exercise (OE), Baduanjin exercise (BE), Pilates exercise (PE), Yoga (YG), Qigong (QG), Dance exercise (DE), Qigong (QG) in improving depression in breast cancer patients.ConclusionThe study revealed that Tai Chi demonstrates positive effects in ameliorating CRF, enhancing quality of life, and alleviating depressive symptoms among breast cancer patients. Moreover, yoga exhibits favorable effects in improving sleep quality in this patient group. Nevertheless, additional randomized controlled trials (RCTs) are warranted in the future to delve deeper into the effectiveness and underlying mechanisms of these exercise interventions.